General expression for the critical seepage gradient in an infinite slope - Federico, A. (Journal of Nepal Geological Society, 2000)
With reference to the ideal case of an infinite slope of granular (c' =0) homogeneous and isotropic soil subject to uniform seepage with a vertical component directed upwards, the possibility, in principle, of a slope instability due to static liquefaction (quick condition) is examined. Such instability takes place when the seepage gradient is the critical one (ic). In this paper, a general expression for ic, is obtained.